Aromatic Back Massage Guidance Improves Knowledge And Skills of Pregnant Women In Preparing For Breastfeeding In Dangin Puri Klod Village, Bali Province - Made Widhi Gunapria Darmapatni; Listina Ade Widyaningtyas; Ni Gusti Kompiang Sriasih; Ni Nyoman Suindri (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
The stunting reduction program is a priority program of the Denpasar City government. The target prevalence of stunting in Denpasar City is expected to reach 4% in 2023. Currently, there are still 482 children with stunting spread across 21 villages/subdistricts in Denpasar City. To achieve this, massive stunting prevention efforts are needed during the first 1000 days of life, starting from pregnancy until the child is 2 years old. Exclusive breastfeeding is an important factor in child nutrition. One of the problems faced in breastfeeding is feeling that there is not enough breast milk to meet the baby's needs. This community service aims to identify knowledge and skills before and after guidance. The activity will take place from August to September 2025. The target is pregnant women in Dangin Puri Klod Village, Bali. Aromatic Back Massage guidance is a combination of 5 basic massage techniques with aromatic oil along the spine, providing a relaxing effect and stimulating the ejection of prolactin and oxytocin. The guidance had an impact on increasing the knowledge and skills of the target group. Direct guidance for pregnant women provided many opportunities to share experiences and knowledge within the group. Updated information encouraged pregnant women to be more enthusiastic in participating in activities and practicing what they had learned. Information media also played an important role in maintaining the knowledge and skills of pregnant women in preparing for the breastfeeding period